Transformation of Agricultural Social Structure and Modifi cation of Meaning and Negotiation of Woman: A Study of the Expansion of Married Woman Card Party in a Sub-district of Nakhon Si Thammarat Province (in Thai) - Sukkhao, Khanuengnit (Asia Social Issues, 2013)
This research was aimed at studying how the expansion of card parties in rural communities in southern Thailand is associated with changes in the structure of agricultural society in order to identify modification of meanings and negotiations among women in this regard. The study areas were four villages in Nakhon Si Thammarat Province. The study suggests that in agricultural society in the past, women were assigned household tasks which consumed their entire day, and the economic structure in the past forced households to do a lot of food production because their life was based on a subsistence economy. Households had to do food production continuously throughout the day and women were also involved in the production in addition to their household tasks. Household-related tasks outside the home or activities that consumed a large amount of time and were not related to their occupations were assigned to men. Accordingly, gambling was an activity that only men took part in upon the change in the structure of agricultural society, women have become more independent from food production and the burden of household tasks. In addition, changes in ideas and the structure of relationships among people in rural areas have resulted from development that connects rural areas to big cities, existence of small towns in rural areas, flow of information without borders into rural areas, and influx of more people from outside into rural areas through the tourism business. Children have been taken care of by the government through the child care center since they were very young. As a result, women have changed their ideas and their pastime. Accordingly, they desire to spend their free time to show their identity in a new way. Since prices of para rubber greatly increased and households took much less time to finish their tasks each day, the conditions for women’s use a card party as means to express their identity have become broader. The conditions include having a lot of free time each day and having money for daily personal use. Women can start their card parties by using traditions as their space for playing cards, so that they can construct a meaning of card playing: a culture. Later, they can extend its meanings; they define it as a daily activity that is not intervened by men and police officers in the villages. Therefore, there are a lot of married women who express their identity through the card parties. However, they do not have power for negotiating with men or their husband equally. This is related to factors in their family. The first important factor is the extent of their role in supervising their family’s economy. The second is that men and women want freedom of expression in this modern society without intervention by the other party. การเปลี่ยนแปลงโครงสร้างสังคมเกษตร กับการสร้างความหมายและการต่อรองของผู้หญิง: ศึกษากรณีการขยายตัวของวงไพ่ผู้หญิง ที่มีครอบครัวแล้วในตำบลแห่งหนึ่ง ของจังหวัดนครศรีธรรมราช ในสังคมเกษตรกรรมแต่เดิมผู้หญิงจะถูก กำหนดให้ต้องมีภารกิจต่อครอบครัวตลอดทั้งวัน โดยโครงสร้างทางเศรษฐกิจนั้นกำหนดให้ ครัวเรือนต้องทำการผลิตหลายอย่าง เนื่องจากตั้งอยู่บนฐานเศรษฐกิจแบบเลี้ยงตัวเอง ทำให้ครัวเรือนต้องทำงานในส่วนการผลิตต่อเนื่องไป ตลอดในแต่ละวันซึ่งผู้หญิงก็มีส่วนในการผลิต นี้ด้วยอีกทั้งผู้หญิงต้องรับผิดชอบภารกิจงาน บ้านการเรือนเพิ่มขึ้นอีก ทำให้ผู้หญิงต้องมีภารกิจตลอดทั้งวัน หากมีภารกิจใดของครอบครัวที่ต้องไปทำาข้างนอก กิจกรรมที่เสียเวลามากและไม่ช่วยสร้างสรรค์เรื่องอาชีพ ก็มีแต่ผู้ชายเท่านั้นที่ทำเป็นหลัก การพนันจึงมีผู้ชายเท่านั้นที่เล่นได้ เมื่อโครงสร้างสังคมของ ภาคเกษตรกรรมเปลี่ยนไป ความเป็นอิสระของผู้หญิงที่ถูกผูกติดอยู่กับ การผลิตและภาระที่มีต่อครอบครัวก็ลดน้อยลง ประกอบกับการพัฒนา ที่เชื่อมโยงภาคชนบทเข้ากับเมืองใหญ่มากขึ้น การเกิดเมืองเล็ก ๆ ขึ้น มากในชนบท การหลั่งไหลของข้อมูลข่าวสารแบบไร้พรมแดนเข้าสู่ ชนบทมากขึ้น การหลั่งไหลของคนจากภายนอกเข้าไปชนบทมากขึ้นผ่าน ธุรกิจการท่องเที่ยว ก็ส่งผลให้เกิดการเปลี่ยนแปลงความคิดและ โครงสร้างความสัมพันธ์ของคนในชนบทอย่างมาก ในขณะที่เด็ก ๆ ในครอบครัวก็ได้รับการดูแลจากรัฐตั้งแต่ยังเล็ก ๆ โดยศูนย์ดูแลเด็ก เล็ก ดังนั้นผู้หญิงจึงทั้งเปลี่ยนแปลงความคิดและการมีเวลาเวลาว่าง ในแต่ละวัน ส่งผลให้ผู้หญิงต้องการใช้เวลาว่างที่เกิดขึ้นแสดงตัวตน ของผู้หญิงแบบใหม่ กระทั่งเมื่อยางพาราราคาดีขึ้นมากและครัวเรือน ใช้เวลาทำงานเพียงเล็กน้อยก็เสร็จสิ้นภารกิจในแต่ละวัน ทำให้เงื่อนไข ที่ผู้หญิงจะใช้วงไพ่เป็นพื้นที่แสดงตัวตนได้เปิดกว้างขึ้น คือมีเวลาว่าง มากในแต่ละวันและมีเงินใช้ส่วนตัวทุกวัน ผู้หญิงสามารถเริ่มต้นวงไพ่ โดยใช้งานประเพณีเป็นพื้นที่การเล่นไพ่ จนสามารถสร้างความหมาย ให้การเล่นไพ่กลายเป็นวัฒนธรรมอย่างหนึ่ง และต่อมาผู้หญิงสามารถ ขยายความหมายให้การเล่นไพ่เป็นกิจกรรมหนึ่งของชีวิตประจำวันที่ไม่ถูกแทรกแซงทั้งจากผู้ชายและเจ้าหน้าที่ตำรวจ ในหมู่บ้านจึงมีผู้หญิงที่มีสามีแล้วออกมาแสดงตัวตนในวงไพ่จำนวนมาก แต่ทั้งนี้ผู้หญิงหรือภรรยาก็ไม่ได้มีอำนาจต่อรองกับผู้ชายหรือสามีได้เท่ากันทั้งหมดขึ้นอยู่กับเงื่อนไขของแต่ละครอบครัว เงื่อนไขที่สำคัญก็คือผู้หญิงมีบทบาทในการควบคุมเศรษฐกิจของครอบครัวได้มากน้อยแค่ไหน นอกจากนี้ก็ได้แก่เงื่อนไขที่แต่ละฝ่ายต้องการอิสระในการแสดงออกในสังคมสมัยใหม่ได้โดยที่อีกฝ่ายหนึ่งไม่ขัดขวาง